MO472A PRELIMINARY STUDY OF POTENTIAL BIOMARKERS FOR EARLY DIAGNOSIS IN CHRONIC KIDNEY DISEASE. (29th May 2021) - Lousa, Irina; Valente, Maria João; Rocha, Susana; D. Viana, Sofia; Preguiça, Inês; Mira, Filipe; Nogueira, Rui; Coimbra, Susana; Catarino, Cristina; Rocha-Pereira, Petronila; Bronze-da-Rocha, Elsa; Faria, Maria do Sameiro; et al.
Abstract: Background and Aims: The conventionally used biomarkers for chronic kidney disease (CKD) diagnosis are not very sensitive for early diagnosis. Their values become clinically significant only when kidney damage is advanced, and a substantial filtration capacity has been lost. The reliance on these biomarkers may result in a long-time lapse in diagnosis, compromising the earlier use of successful therapeutic interventions to prevent CKD progression and reduce the risk of other common comorbidities. The study of earlier and more sensitive biomarkers for CKD diagnosis is an important medical need. Potentially new biomarkers reflecting different pathophysiological processes underlying CKD, such as changes in renal function, tubulointerstitial injury, inflammation and fibrosis, have been proposed. The use of a panel of biomarkers is likely to be synergetic in detecting CKD, since there are several different mechanisms by which CKD can initiate. Our aim was to identify markers of renal damage/dysfunction and evaluate their sensitivity for CKD detection, in patients at the earlier stages of the disease, stages 1 and 2. Method: This study included 32 healthy controls and 29 CKD patients at stages 1 and 2, categorized according to the KDIGO guidelines, using the CKD-EPI equation based on serum creatinine to estimate the glomerular filtration rate (GFR). Causes of CKD in the studied patients were diabetes mellitus ( n = 19), polycystic kidney disease ( n = 1) and of unknown cause ( n = 7) or other ( n = 2). Circulating levels of creatinine and β-trace protein (BTP), as markers of renal function; interleukin 6 (IL-6), as a marker of inflammation; tissue inhibitor metalloproteinase 1 (TIMP 1), as a marker of tubulointerstitial injury; pro B-type natriuretic peptide (proBNP), as a marker of cardio-renal dysfunction; and cell-free DNA (cfDNA), as a marker of cellular damage, were evaluated. Results: Compared to controls, we found significantly higher values of all studied markers in CKD patients (stage 1 and stage 2): BTP, TIMP-1, IL-6, pro-BNP, and cfDNA. In CKD patients, GFR was negatively correlated with circulating levels of pro-BNP ( r = -0.610, P = 0.004, n = 20) and cfDNA ( r = -0.408, P = 0.028, n = 29); and, microalbuminuria was positively correlated with circulating levels of BTP ( r = 0.465, P = 0.013, n = 28). The biomarker cfDNA was positively correlated with TIMP-1 ( r = 0.445, P = 0.16, n = 29), a marker of tubulointerstitial injury, and with IL-6 ( r = 0.670, P < 0.001, n = 29), a marker of inflammation. All patients presented at least two of the studied biomarkers with higher values than the median value presented by controls. Of all studied biomarkers, BTP was the one that was most altered in patients (86.2% presented higher values than the highest value presented by controls). Conclusion: Our results suggest that the studied biomarkers are sensitive to the primary response to renal injury, being significantly elevated in the earlier stages of CKD, particularly BTP. Pro-BNP and cfDNA correlate well with disease severity assessed by GFR. The use of a panel comprising several biomarkers, related with different pathophysiological mechanisms underlying CKD initiation and progression, may increase the potential to detect patients at risk, when compared with the evaluation of each biomarker alone. Further validation for the use of these new potential biomarkers requires larger studies with standardized analytical methodologies. Acknowledgments: This work was supported by Applied Molecular Biosciences Unit (UCIBIO) and financed by FEDER COMPETE2020 funds UIDB/04378/2020 and UIDP/04539/2020 (CIBB); by POCI-01-0145-FEDER-007440; by FCT doctoral grant SFRH/BD/145939/2019; by funds from Portugal Regional Coordination and Development Commissions (Norte-01-0145-FEDER-000024).